The Role of Khyber Pakhtunkhwa in the Tradition of Urdu Novel - Shah, Syed Zubair; Khan, Qudrat Ullah (sourcecoder, 2024)
It is said that Fasana e Azad marks the start of Urdu novel, and thereafter, several authors contributed to the novel writing. Every novel represents society and serves as both the beginning and the end of an intellectual journey. Modern vocabulary and diction are also used to enhance contemporary novels. The KPK’s novel writing is the main topic of this article. The notable authors in the KPK novel writing scene can be identified by their novel genre. In KPK, the first Urdu novel was released in 1903. Romantic stories, philosophical debates, Pashtun history and culture, terrorism, and extremism are all featured in KPK novel. These novels have a thematic and technical originality in addition to all of these themes. Even though there aren’t many novels written in KPK, the ones that are now published are enhanced by contemporary themes and techniques. These methods and themes have been the subject of this study article’s detailed concentration.